Metabolic profile of methylazoxymethanol model of schizophrenia in rats and effects of three antipsychotics in long-acting formulation - Horska, Katerina; Kotolova, Hana; Karpisek, Michal; Babinska, Zuzana; Hammer, Tomas; Prochazka, Jiri; Stark, Tibor; Micale, Vincenzo; Ruda-Kucerova, Jana (Toxicology and applied pharmacology, 2020)
Mortality in psychiatric patients with severe mental illnesses reaches a 2-3 times higher mortality rate compared to the general population, primarily due to somatic comorbidities. A high prevalence of cardiovascular morbidity can be attributed to the adverse metabolic effects of atypical antipsychotics (atypical APs), but also to metabolic dysregulation present in drug-naïve patients. The metabolic aspects of neurodevelopmental schizophrenia-like models are understudied. This study evaluated the metabolic phenotype of a methylazoxymethanol (MAM) schizophrenia-like model together with the metabolic effects of three APs [olanzapine (OLA), risperidone (RIS) and haloperidol (HAL)] administered via long-acting formulations for 8 weeks in female rats. Body weight, feed efficiency, serum lipid profile, gastrointestinal and adipose tissue-derived hormones (leptin, ghrelin, glucagon and glucagon-like peptide 1) were determined. The lipid profile was assessed in APs-naïve MAM and control cohorts of both sexes. Body weight was not altered by the MAM model, though cumulative food intake and feed efficiency was lowered in the MAM compared to CTR animals. The effect of the APs was also present; body weight gain was increased by OLA and RIS, while OLA induced lower weight gain in the MAM rats. Further, the MAM model showed lower abdominal adiposity, while OLA increased it. Serum lipid profile revealed MAM model-induced alterations in both sexes; total, HDL and LDL cholesterol levels were increased. The MAM model did not exert significant alterations in hormonal parameters except for elevation in leptin level. The results support intrinsic metabolic dysregulation in the MAM model in both sexes, but the MAM model did not manifest higher sensitivity to metabolic effects induced by antipsychotic treatment.
Keywords: metabolismus lipidů; Schizophrenia; Female; metabolom; antipsychotika; potkani Sprague-Dawley; risperidon; Antipsychotic Agents; Olanzapine; Lipid Profile; Metabolome; Disease Models, Animal; Lipid Metabolism; Antipsychotic; Rats, Sprague-Dawley; Haloperidol; mužské pohlaví; Methylazoxymethanol; zvířata; Adipokine; ženské pohlaví; schizofrenie; Rats; Animals; Methylazoxymethanol Acetate; Male; Risperidone; haloperidol; modely nemocí na zvířatech; olanzapin; methylazoxymethanolacetát